Analysis of the Use of Electric Grab Bike in Creating Smart City Dimensions of Smart Energy in the City of Bandung - Khaerina, Elvina; Astuti, Yuhana; Hidayatulloh, Deden Syarif (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
One of the effects of population density in Indonesia is an increase in the number of domestic motorcycle sales, which directly results in a depletion of fuel oil (BBM) and an increase in air pollution by 2025. One way to overcome this issue is by implementing the smart city concept, with a focus on smart energy dimensions, and by using electric vehicles, such as electric grab bikes. The aim of this study is to determine the value of the smart energy index for the use of electric grab bike in the city of Bandung and its impact on society, particularly in Bandung. The research method employed is a mixed methods approach, utilizing a quadruple helix approach that involves the government, business player, academics, and the community. The results indicate that the value of the smart energy index in the case study of electric grab bike usage in the city of Bandung is 72.15, indicating satisfactory performance, but there are still several areas that require improvement. Additionally, the use of electric grab bike has a positive impact, such as reduced fuel consumption, greater environmental friendliness, reduced urban noise, and affordable electric fuel rates that benefit the community.